Analysis of Economic Structure and Labor Absorption: A Study in North Maluku - Prince Charles Heston Runtunuwu; Norsaidatul Akmar Mazelan (Journal of Loomingulisus ja Innovatsioon, 2024)
The purpose of this study is (1) to analyze the pattern of shifting economic structures in Pulau Taliabu Regency for the period 2016-2020 and (2) to analyze the impact of shifting economic structures on labor absorption in Pulau Taliabu Regency, North Maluku in 2016-2020. Secondary data in this study were obtained from BPS North Maluku and BPS Data for Pulau Taliabu Regency. Data collection carried out in this study was carried out by issuing a research permit letter to the relevant agencies, namely the central office (BPS) and related agencies in Pulau Taliabu Regency. The analysis technique used in this study uses Shift Share Analysis, which is an analysis that aims to determine the performance or productivity of regional economic work by comparing it with larger areas (regional or national). Changes in Economic Structure in Labor Absorption in Pulau Taliabu Regency Based on the results of the Shift Share analysis, the GRDP of Pulau Taliabu Regency increased during the period 2016-2020 by IDR 84,127.50 million. When viewed from the contribution to GRDP, it shows a change in the economic structure from the primary sector, namely agriculture, amounting to Rp. 38,246.00 million to the secondary sector, namely electricity and gas procurement of Rp. 2,807.50 million or the tertiary sector, namely company services of Rp. 29,774.17 million. The agricultural sector is quite capable of providing a positive contribution to economic growth in Pulau Taliabu Regency, due to the development and construction of related regulations and the high dynamics of changes in the use of space that have an impact on land acquisition in the years to come. Based on the hypothesis proposed, the results of the study based on field facts can be accepted, so it can be concluded that the Economic Structure of Pulau Taliabu Regency has experienced a shift towards the Primary, secondary and tertiary sectors.